Removal of Basic Red 18 onto modified sepiolite: Equilibrium, adsorption kinetics and thermodynamic studies - Turunc, Ersan (European Journal of Chemistry, 2015)
The adsorption of Basic Red 18 (BR 18) from aqueous solution onto KF modified sepiolite was carried out as a function of pH, initial dye concentration, contact time and temperature. The equilibrium data were evaluated according to Langmuir and Freundlich models. The experimental results showed that the best correlation was obtained on Freundlich model. The adsorption kinetics was examined with pseudo-first order, pseudo-second order and intraparticle diffusion models. The result was best fitted for pseudo-second order kinetic model. Thermodynamic investigations were also performed to determine ΔH°, ΔG° and ΔS°. The results indicated that the adsorption of BR 18 was exothermic and spontaneous.